2004
DOI: 10.1016/s0212-6567(04)78922-2
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de una intervención informativa a hipertensos mediante mensajes de alerta en el teléfono móvil (HTA-ALERT)

Abstract: The telephone messaging intervention with alerts and reminders sent to mobile phones did not improve compliance with therapy in patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 5 publications
1
51
0
3
Order By: Relevance
“…Five studies identified as RCT, one as quasi-experimental. All studies took place internationally, more specifically two in Spain, 17, 18 one in Russia, 19 one in China, 20 one in South Korea, 21 and one in the Philippines. 22 The studies’ targeted behaviors included a partial or sole focus on HTN management, while two of the studies also focused on weight loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies identified as RCT, one as quasi-experimental. All studies took place internationally, more specifically two in Spain, 17, 18 one in Russia, 19 one in China, 20 one in South Korea, 21 and one in the Philippines. 22 The studies’ targeted behaviors included a partial or sole focus on HTN management, while two of the studies also focused on weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…The SMS component of each study was classified as either the main or a supplemental component of the intervention. Only one study integrated SMS into its intervention as a supplemental component, 20 while the other five used SMS as the main component, with 18,19 or without 17, 21,22 non-SMS supplemental components. For example, the Lin study integrated a supplemental SMS component, sending patient-participants daily SMS to track their weight loss goal progress, with supporting education sessions and telephone coaching call components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Several studies have shown that mobile text message reminders can increase attendance at healthcare appointments 11, 12 as well as patient adherence to follow-up appointments. 13, 14 Text messages also have been used to improve medication adherence for patients with chronic medical conditions 15 such as cardiovascular disease, 16 coronary heart disease, 17 diabetes, 18, 19 hypertension, 20 asthma, 21 allergic rhinitis, 12 HIV, 22, 23 or schizophrenia. 24 Although some studies have not shown improvements in outcomes associated with text messaging, 25, 26 others have found that text messages significantly improved allergic rhinitis symptoms, 12 asthma control, 27 diabetes control, 28, 29 or hematologic parameters in children with sickle cell anemia receiving hydroxyurea.…”
Section: Introductionmentioning
confidence: 99%
“…28 Most studies focused on improving medication adherence using mobile phones have been limited to improving unintentional nonadherence through reminder messages, and results of these investigations have been mixed in terms of the effect on medication use. 2934 However, a limited number of studies have incorporated the tailoring of health messages into interventions focused on medication nonadherence. Petrie and colleagues (2012) showed improved medication adherence to controller inhalers among adult patients with asthma by text messaging subjects from 1 to 3 times daily over 18 weeks.…”
Section: Introductionmentioning
confidence: 99%